International environmental governance for the 21st century: Challenges, reform process and options for action on the way to Rio 2012 - Nils Simon (Stiftung Wissenschaft und Politik (SWP), 2011)
The institutional landscape of international environmental governance is going to be reassessed at the United Nations Conference on Sustainable Development in Rio 2012. A substantial overhaul is overdue. At present, the system neither ensures sufficient protection of global environmental goods, nor does it enable sustainable use of threatened ecosystems. These failures are due to a fragmented governance architecture comprising almost 500 multilateral environmental agreements, poor coordination among the many involved UN organizations, and insufficient funds for responsible agencies, especially the UN Environment Programme. In light of these failures, the European Union favors a comprehensive reform. The institutional core is supposed to be strengthened with the foundation of a UN Environment Organization. Brazil has introduced the proposal to create an "umbrella" structure for environment and sustainable development. The USA, though, disapprove such a substantial revision including a new UN specialized agency, as long as its added value has not been laid out clearly. To find common ground, three intergovernmental consultative processes have been conducted since 2006. During these, government officials agreed upon central functions the system ought to be fulfilling. Yet the form of a renovated governance architecture remains contested. A consensus might be in reach if Europe shows political leadership and further enhances its reform model. At the same time, though, delegates must move with caution in order to convince the more skeptical partners. If they succeed at this task, the general structure of a revised environmental governance system might be agreed upon by 2012
Keywords: 320